Young Women, Sexual Behaviour and Sexual Decision-Making - Lesley Hoggart (Forum: Qualitative Social Research, 2006)
This paper considers young people's sexual decision-making in the context of New Labour's policies on teenage pregnancy. In 1999, the newly formed Social Exclusion Unit sought to understand why the UK had the highest number of teenage conceptions in Europe (SEU 1999). One of the conclusions was that young people in the UK are engaging in "risky" rather than "safe" sex. Although New Labour has since developed policies designed to help young people avoid what is seen as risky sexual activity, there is a tension in sexual health policy between the overall aim of providing young people with the knowledge and confidence to practice "safe sex", and an underlying belief amongst many in the undesirability of "underage sex". This is partly a legacy of disagreements evident in the 1980s and 1990s when some organisations argued against sex education and contraceptive provision for young people on the grounds that it encouraged promiscuous and risky behaviour. The paper shows how alternative meanings of risk and responsibility are present in young mothers' own representations of their sexual decision-making. It does this through an analysis of two research projects on Young Women, Sex and Choices. URN: urn:nbn:de:0114-fqs0601283